Answers

The Brainliest Answer!
  • Brainly User
2016-07-03T19:36:24+08:00
Solution:

k + 2 - (5k - 34) = 3k - 11 - (k + 2)
k + 2 - 5k + 34 = 3k - 11 - k - 2
k - 5k + 2 + 34 = 3k - k - 11 - 2
-4k + 34 =2k - 13
-4k - 2k = -13 - 34
-6k = -49
-6k/-6 = -49/-6

k = 49/6   ⇒   ANSWER

Check:
k = 49/6
a₁ = 5k - 34
    = 5(49/6) - 34    (convert to similar fractions)
    = 245/6 - 204/6
    = 41/6

a₂ = k + 2
    = 49/6 + 2      (convert to similar fractions)
    = 49/6 + 12/6
    = 61/6

a₃ = 3k - 11
    = 3 (49/6) - 11
    = 147/6 - 66/6
    = 81/6

The sequence:  41/6,  61/6,   81/6
Common difference:  20/6
  
1 5 1